Pengaruh Model Pembelajaran Project Based Learning Terhadap Hasil Belajar Etika Profesi - Arum, Erika Ananda; Darmawati, Desak Made (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The purpose of this study is to improve student learning outcomes in professional ethics subjects by using a project-based learning model. The implementation of this research was carried out at SMK Pusaka 1 Jakarta. This research method uses Quasi-Experimental Design with the design Non-non-equivalent pretest and posttest-only Control Group Design. The overall population is 31 students with sample selection using the Non-Probability Sampling technique, one of the techniques is saturated sampling. The research sample of X AKL1 students totaling 16 students as an experimental class using the project-based learning model and X AKL2 with a total of 15 students as a control class using conventional methods. Data collection uses observation and multiple-choice questions (PG). The hypothesis test carried out obtained a value of Sig. (2-tailed) 0.012 < 0.05, then Ho was rejected and H1 was accepted. The conclusion obtained in this study is that there is an influence in the use of the project-based learning model on the learning outcomes of professional ethics X Accounting at SMK Pusaka 1 Jakarta.